The Use of Audio Visual Learning Media for Trainees at the Balai Besar Pelatihan Kesehatan (BBPK) Makassar - Maryam Maryam; Tuti Bahfiarti; Muliadi Mau (IHSA Institute, 2024)
Communication plays an important role in the world of education, this research will discuss the training aspect. Communication facilitates the exchange of information between educators and trainees to achieve learning goals. One of the factors that contributes to the effectiveness of communication in the teaching and learning process is the use of learning media. This media is used as a means to convey messages from educators (communicators) to training participants (audience). This research aims to evaluate the extent of use of audio-visual learning media by training participants at BBPK Makassar. The research method used is a quantitative approach with descriptive statistical analysis to describe and summarize statistical data. The research results show that the majority of participants predominantly use audio-visual learning media in the high category, namely 62.9% of the total number, while in the medium category with an assessment of 36.5% and the remaining 0.6% in the low category. This research also displays tabulated data on the use of audio-visual learning media by training participants based on various factors, such as gender, age, length of service, highest level of education, agency of origin, type of job/profession, learning style, and training methods.